Spleen Oxylipin and Polyunsaturated Fatty Acid Profiles are Altered by Dietary Source of Polyunsaturated Fatty Acid and by Sex. Issue 3 (7th April 2020) - Pauls, Samantha D.; Ragheb, Mariam; Winter, Tanja; Leng, Shan; Taylor, Carla G.; Zahradka, Peter; Aukema, Harold M.
Abstract: As the largest secondary lymphoid organ, the spleen plays an important role in immune responses. The role of arachidonic acid (ARA) and its 20‐carbon eicosanoids in modulating immune function has long been of interest. However, recent advances have enabled the identification of numerous other n‐6 and n‐3 polyunsaturated fatty acid (PUFA)‐derived oxylipins. Here, we investigate the effects of diet and sex on the spleen nonesterified oxylipin profiles and phospholipid and neutral lipid PUFA composition in Sprague–Dawley rats supplemented with oils rich in α‐linolenic acid (ALA), eicosapentaenoic acid (EPA), docosahexaenoic acid (DHA), or linoleic acid. Dietary ALA, EPA, and DHA resulted in lower levels of ARA and ARA oxylipins. Oxylipins derived from other n‐6 PUFA were also reduced despite no or opposite effect on their PUFA levels. Each diet also resulted in higher levels of oxylipins almost exclusively derived from the supplemented PUFA, despite PUFA in the same biosynthetic pathway also often being increased. Further, while oxylipin differences often reflected changes to phospholipid PUFA, there were instances where they corresponded more closely to changes in neutral lipid PUFA. With respect to sex effects, >50% of lipoxygenase ARA‐derived oxylipins were higher in males in at least one diet group, while multiple DHA oxylipins were lower in males only in rats provided the DHA diet. This fundamental description of oxylipin composition in the spleen, including the influence of diet and sex and the relationship to PUFA composition, will help inform future studies examining the functions of these oxylipins under physiological and pathological conditions.